BID Mediates Oxygen-Glucose Deprivation-Induced Neuronal Injury in Organotypic Hippocampal Slice Cultures and Modulates Tissue Inflammation in a Transient Focal Cerebral Ischemia Model without Changing Lesion Volume - Martin, Nellie Anne; Bonner, Helena; Elkjær, Maria Louise; D’Orsi, Beatrice; Chen, Gang; König, Hans Georg; Svensson, Martina; Deierborg, Tomas; Pfeiffer, Shona; Prehn, Jochen H.; Lambertsen, Kate Lykke (Frontiers in Cellular Neuroscience, 2016)
The BH3 interacting-domain death agonist (BID) is a pro-apoptotic protein involved in death receptor-induced and mitochondria-mediated apoptosis. Recently, it has also been suggested that BID is involved in the regulation of inflammatory responses in the central nervous system. We found that BID deficiency protected organotypic hippocampal slice cultures in vitro from neuronal injury induced by oxygen-glucose deprivation. In vivo, BID-knockout (KO) mice and WT mice were subjected to 60 minutes of transient middle cerebral artery occlusion to induce focal cerebral ischemia, and allowed to recover for 24 hours. Infarct volumes and functional outcome were assessed and the inflammatory response was evaluated using immunofluorescence, Western blotting, quantitative PCR and Mesoscale multiplex analysis. We observed no difference in the infarct volume or neurological outcome between BID-KO and WT mice. The inflammatory response was reduced by BID deficiency as indicated by a change in microglial/leukocyte response. In conclusion, our data suggest that BID deficiency is neuroprotective in an in vitro model and modulates the inflammatory response to focal cerebral ischemia in vivo. However, this is not translated into a robust neuroprotection in vivo.